Q: 6X equals X plus 15 equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

5x+15 = 6x-10 5x-6x = -10-15 -x = -25 x = 25

x=4/3

-15 = 6x + 3 - 3-15 = 6x (3 - 3 = 0)-2.5 = x (-15/6)

5x + x - 6x + 2x = 2x

2x + 15 = 8x + 43 -6x = 28 x = -6 / 28 = -3 / 14

Related questions

x+15+(-15)=6x+(15+(-15)=6x+(15-15)=6x+(0)=6x+0=6Add/subtract 0 from both sides,x=6

5x+15 = 6x-10 5x-6x = -10-15 -x = -25 x = 25

6x-x+15-9= 6x-x=5x 15-9=6 5x+6=0 5x=-6 x=-1.2

9x+6 = 6x+15 9x-6x = 15-6 3x = 9 x = 3

x=4/3

-15 = 6x + 3 - 3-15 = 6x (3 - 3 = 0)-2.5 = x (-15/6)

6x+x = 7x

It is: y = 5x+15

11

8x = 2x + 15 6x = 15 x = 15/6 = 2.5

x=-9 15 + x = 6x + 60 x = 6x + 45 -5x = 45 x = -9 15 + (-9) = (6 * (-9)) + 60 15 - 9 = -54 + 60 6 = 60 - 54 6 = 6 There is no answer because, 15+x=6x+60 -15 -15 x=6x+45 Which is imposible because "x" can't equal itself times six plus forty-five.

5x + x - 6x + 2x = 2x